Conducting microhelices from self-assembly of protein fibrils. Issue 25 (7th June 2017) - Bäcklund, Fredrik G.; Elfwing, Anders; Musumeci, Chiara; Ajjan, Fátima; Babenko, Viktoria; Dzwolak, Wojciech; Solin, Niclas; Inganäs, Olle
Abstract : Self-assembly of conducting polymer onto chiral amyloid superstructures. Abstract : Herein we utilize insulin to prepare amyloid based chiral helices with either right or left handed helicity. We demonstrate that the helices can be utilized as structural templates for the conducting polymer alkoxysulfonate poly(ethylenedioxythiophene) (PEDOT-S). The chirality of the helical assembly is transferred to PEDOT-S as demonstrated by polarized optical microscopy (POM) and Circular Dichroism (CD). Analysis of the helices by conductive atomic force microscopy (c-AFM) shows significant conductivity. In addition, the morphology of the template structure is stabilized by PEDOT-S. These conductive helical structures represent promising candidates in our quest for THz resonators.